Spectral characteristics of the high-resolution liver CT data - Kurbel, Sven (Radiology and oncology (Ljubljana), 1999)
Background. Statistical methods and Fourier analysis of CT values were used todetect presence of liver cirrhosis and of iron-overload in the sets of high-resolution liver CT data. Subjects and methods. Eleven liver cirrhosis patients, seven hemodialysed patients with iron-overload and 51 control individuals were included. CT unit SIEMENS SOMATOM DRH was used (kernel 2, 0.2mm wide and 2 mm thick pixels). Square sample areas, 50 pixels wide, two per control and three per patient were collected. The areas statistically analysed and decomposed in 100 linear fragments (50 lines and 50 columns of 50pixels) gor Fourier analysis. The mean and standard devations of harmonic powers were calculated for each sample. The high-resolution CT data in the iron-overload patients different from the controls by the increased mean density (>-79 HU) and reduced power of many harmonics (p<0.01). The high-resolution CT data of the cirrhotic patients showed the decreased mean density (<50 HU) and increased power of harmonics from 0.1 t0 0.9 cycles/mm (wavelengths from 10 to 1.1 mm) (p <0.01). Conclusions. Information extractable from the high-resolution liver CT data can distinguish between thenormal and cirrhotic, or iron-overload livers.
Keywords: Fourier analysis; Hemodialysis; Iron overload; Liver cirrhosis; Tomography, x-ray computed